Kompetensi Profesional Guru Bimbingan dan Konseling Berdasarkan Persepsi Guru Mata Pelajaran - Merlina Mbari; Gracianus Edwin Tue P Lejap; Wens Nagul (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to evaluate subject teachers' perspectives on the professional competence of guidance and counseling (BK) teachers at SMAN 4 Kupang for the 2024/2025 academic year. The professional competencies studied include the ability to conduct assessments, mastery of theory, design and implement guidance programs, evaluation, and the application of ethics in the profession. These competencies are considered important because they measure the quality of BK teachers in helping students overcome various problems, both academic and non-academic. The method used in this study is a descriptive qualitative approach supplemented by quantitative data to obtain a more comprehensive and objective picture. The sample in this study consisted of 77 subject teachers selected using a purposive sampling technique based on their direct involvement in the teaching and learning process and interactions with BK teachers. Data were collected through questionnaires to obtain quantitative information, observations to assess field practices, interviews to deepen views, and documentation to supplement empirical evidence. Data analysis was carried out using frequency distributions, calculations of means, standard deviations, and 5% confidence intervals to ensure the accuracy of the results. In addition, qualitative analysis was conducted using data triangulation to ensure more valid and accountable interpretations. The research findings indicate that the professional competency scores of guidance and counseling teachers fall into the high category, with an average score of 263.61 and a confidence interval of 259.61–267.60.